Modification method of CoAl-based lithiated spinel coated high-nickel positive electrode material
By forming a CoAl-based lithiated spinel layer on the surface of the high-nickel cathode material, the structural degradation and battery performance decay caused by volume changes during charging and discharge process are solved, and the structural stability and electrochemical performance of the material are significantly improved.
Patent Information
- Application Number
- CN202411807700.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-08
AI Technical Summary
The volume of high-nickel cathode materials changes dramatically during charging and discharging, resulting in structural degradation, mechanical failure, thermal instability and battery performance decay.
The material modification is achieved by forming a CoAl-based lithiated spinel layer on the surface of the high-nickel positive electrode material. The method includes preparing a modified solution according to a stoichiometric ratio of Li2Co1.6Al0.4O4, dispersing the high nickel positive electrode material in the solution, evaporate and drying with a stirring, and then sintering to form a CoAl-based lithiated spinel cladding.
The modified CoAl-based lithiated spinel-coated high-nickel cathode material has excellent structural stability and electrochemical properties, and exhibits high capacity and first-round charge and discharge efficiency at high voltages, significantly improving the cycling stability and thermomechanical stability of the material.
Smart Images

Figure CN119774669A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a modification method of a CoAl-based lithiated spinel-coated high-nickel positive electrode material. Background Art
[0002] In the field of lithium-ion batteries, high-nickel cathode materials have attracted much attention due to their high energy density. However, their inherent thermal, chemical and mechanical instabilities have become the main obstacles to their commercial applications, especially potential risks in terms of safety. Specifically, the volume change problem of high-nickel cathode materials during charging and discharging is particularly significant. With the increase of nickel content, the volume change of the material intensifies. This drastic volume expansion and contraction not only affects the long-term cycle stability of the battery, but may also cause material structural degradation and mechanical failure. For example, during the charging process, the volume expansion of the cathode material can lead to loosening and contact failure between particles, and the electrochemical performance of the battery will decrease significantly over time. In addition, the lattice contraction along the c-axis direction of the crystal caused by the increase in nickel content can easily lead to stacking faults or the formation of different phases. These structural changes directly lead to material deactivation and capacity decay.
[0003] Moreover, the local volume changes in high-nickel cathode materials are often non-uniform, causing local strain accumulation and concentration, leading to the formation of multi-scale cracks, such as intergranular cracks and intragranular cracks. The expansion of these cracks destroys the integrity of the electrode and accelerates the degradation of battery performance. During the cycle process, the accumulation of cracks not only aggravates material degradation, but also leads to an increase in the internal resistance of the battery and a decrease in discharge performance, affecting the efficiency and service life of the entire battery system.
[0004] In addition, high-nickel cathode materials have poor heat resistance in the de-lithiation state. The redox reaction during the de-lithiation process causes the release of active oxygen on the surface of the material, such as oxygen and high-valent nickel ions (Ni4+). These oxidizing substances not only cause further degradation of the material, but may also increase the thermal instability of the battery and cause the risk of thermal runaway. Under high voltage or high temperature conditions, the oxidation of the material increases, and problems such as cracking and shedding occur on the surface, further exacerbating the thermal runaway phenomenon.
[0005] At present, although researchers have discovered extremely low volume change characteristics in non-layered structural materials, such as disordered salt rock structure positive electrode materials and partially disordered spinel structure materials, these materials still face challenges in adapting to the bulk lattice characteristics. In order to better adapt to the bulk lattice characteristics, the surface coating or bulk composite structure needs to have the same oxygen anion framework and similar lattice parameters to achieve coherent growth. The spinel structure has a strong metal-oxygen covalent bond, which can capture released oxygen atoms and prevent the spontaneous oxygen evolution of high-nickel positive electrode materials at higher voltages, thereby ensuring the thermal and mechanochemical stability of the structure. However, there is no effective solution in the prior art that can comprehensively solve the above problems of high-nickel cathode materials. Summary of the invention
[0006] The purpose of the present invention is to propose a modification method for a CoAl-based lithiated spinel-coated high-nickel positive electrode material in view of the problems existing in the background technology. The modification method of the present invention is simple, the raw materials are extensive, and the high-nickel positive electrode material coated with the CoAl-based lithiated spinel has excellent structural stability and electrochemical properties, especially at high voltage, it can obtain a higher capacity and first-cycle charge and discharge efficiency.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A method for modifying a high-nickel cathode material coated with a CoAl-based lithiated spinel, wherein a CoAl-based lithiated spinel layer is formed on the surface of the high-nickel cathode material to achieve modification of the high-nickel cathode material; wherein the chemical formula of the CoAl-based lithiated spinel is Li2Co 1.6 Al 0.4 O4.
[0009] A method for modifying a CoAl-based lithiated spinel-coated high-nickel positive electrode material comprises the following steps:
[0010] Step 1. Follow the Li2Co 1.6 Al 0.4 The stoichiometric ratio of O4 is 5 mmol / L to 12 mmol / L, lithium acetate, cobalt acetate and aluminum nitrate are weighed and dissolved in ethanol, and stirred to dissolve to obtain a modified solution; in the modified solution, the molar concentration of lithium acetate is 5 mmol / L to 12 mmol / L;
[0011] Step 2. Disperse the high nickel cathode material in the modified solution prepared in step 1, stir and mix evenly to obtain a mixed solution; wherein Li2Co 1.6 Al 0.4 O4 accounts for 3wt% to 5wt% of the mass of the high nickel positive electrode material;
[0012] Step 3. Raise the temperature of the mixed solution to 80°C, and evaporate the mixed solution at 80°C under vigorous stirring to obtain a powder, which is then dried;
[0013] Step 4. Grind the powder after the drying treatment in step 3, sinter it, and then naturally cool it to room temperature to obtain a CoAl-based lithiated spinel-coated high-nickel positive electrode material.
[0014] Further, in step 1, the molar ratio of lithium acetate, cobalt acetate and aluminum nitrate is Li2Co 1.6 Al 0.4 Stoichiometric ratio of O4.
[0015] Furthermore, in step 3, the stirring speed is set to 500-700 r / min.
[0016] Furthermore, in step 3, the drying process is carried out in a vacuum environment, the drying temperature is 70 to 90° C., and the time is 10 to 14 hours.
[0017] Furthermore, in step 4, the sintering treatment is carried out in an oxygen atmosphere, at a temperature of 400 to 500° C., for a time of 5 to 10 hours.
[0018] Preferably, in step 4, during the sintering process, the heating rate is 3-5°C / min.
[0019] The present invention also provides the use of the CoAl-based lithiated spinel-coated high-nickel positive electrode material obtained by the above-mentioned modification method in a lithium ion battery.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The method for surface coating and modification of high-nickel positive electrode materials of the present invention is simple and easy to operate, and the raw materials are widely available and have good repeatability.
[0022] 2. The modified CoAl-based lithiated spinel-coated high-nickel positive electrode material of the present invention has excellent structural stability and electrochemical performance, and has the advantages of high specific capacity and high first-cycle charge and discharge efficiency at a high cut-off voltage.
[0023] 3. The present invention coats the surface of the high-nickel positive electrode material with CoAl-based lithiated spinel. The CoAl-based spinel is a structure compatible with the positive electrode lattice, has extremely low strain, can promote the rapid migration of lithium ions, and ensures the stability of the structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The SEM images of the samples obtained in Example 1 at different magnifications;
[0025] Figure 2 This is the EDS-Mapping diagram of the sample obtained in Example 1;
[0026] Figure 3 is the XRD pattern of the sample obtained in Example 1;
[0027] Figure 4 The first cycle charge-discharge diagram (a and b) and dQ / dV diagram (c and d) of the sample obtained in Example 1 at different cut-off voltages;
[0028] Figure 5 This is a comparison chart of the capacity retention rate of the samples obtained in Example 1 after 200 cycles at 1C rate;
[0029] Figure 6 This is the DCR test graph of the sample obtained in Example 1 after 50 cycles;
[0030] Figure 7 This is the EIS test graph of the sample obtained in Example 1 after 50 cycles;
[0031] Figure 8 The SEM images of the samples obtained in Example 2 at different magnifications;
[0032] Fig. 9 This is the EDS-Mapping diagram of the sample obtained in Example 2;
[0033] Fig.10 XRD pattern of the sample obtained in Example 2. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0035] Example 1
[0036] A method for modifying a CoAl-based lithiated spinel-coated high-nickel positive electrode material comprises the following steps:
[0037] Step 1. Follow the Li2Co 1.6 Al 0.4 The stoichiometric ratio of O4 is 1:1, lithium acetate, cobalt acetate and aluminum nitrate are weighed and dissolved in ethanol, and stirred to dissolve to obtain a modified solution; in the modified solution, the molar concentration of lithium acetate is 6.89mmol / L;
[0038] Step 2. Disperse the high nickel cathode material in the modified solution prepared in step 1, stir and mix evenly to obtain 50 mL of pink mixed solution; wherein Li2Co 1.6 Al 0.4 O4 accounts for 3wt% of the mass of the high nickel cathode material;
[0039] Step 3. The mixed solution was heated to 80°C, and the mixed solution was evaporated at a stirring speed of 600 r / min and a temperature of 80°C to obtain a powder, and the powder was vacuum dried in a vacuum oven at 80°C for 12 hours to remove the solvent;
[0040] Step 4. Grind the dried powder obtained in step 3, place it in a tube furnace, and sinter it at 450°C for 5 hours in an oxygen atmosphere. The heating rate is set to 5°C / min. After sintering, cool it naturally to room temperature to obtain a CoAl-based lithiated spinel-coated high-nickel positive electrode material (3wt%-NMC92).
[0041] Figure 1 This is the SEM spectrum of the high-nickel positive electrode material coated with 3% CoAl lithiated spinel in Example 1. It can be seen from the figure that the spherical particles are basically maintained at about 10-15μm, and a white film-like substance appears on the spherical surface, indicating the presence of coating substances, and some spherical particles have slight corrosion on the surface.
[0042] Figure 2 This is the EDS-Mapping spectrum of the high-nickel positive electrode material coated with 3% CoAl lithiated spinel in Example 1. As can be seen from the figure, the nickel, cobalt and manganese elements are evenly distributed without segregation, and the energy spectrum of the aluminum element shows the successful incorporation of the surface aluminum element. Content analysis shows that due to the presence of a layer of cobalt-based spinel on the surface, the surface nickel, cobalt and manganese ratio deviates from the original sample ratio, and the cobalt content increases, proving the coating behavior of the surface structure.
[0043] Figure 3 This is the XRD pattern of the high nickel positive electrode material coated with 3% CoAl lithiated spinel in Example 1. As can be seen from the figure, the sample exhibits a layered structure corresponding to the R3m space group, and no impurity phase appears.
[0044] Figure 4 The first cycle charge and discharge diagram and dQ / dV diagram of different cut-off voltages of 3% CoAl lithiated spinel coated high nickel positive electrode material in Example 1 are shown. The specific test conditions are: 0.1C / 0.1C charge and discharge test was performed at 25°C and the voltage range was 2.7~4.3V and 2~4.5V. It can be seen from the figure that the first discharge capacity at 4.3V reaches 223mAh / g, and the first charge and discharge efficiency is 86%. The first discharge capacity at 4.5V reaches 230mAh / g, and the first charge and discharge efficiency is 88%. Both have been greatly improved compared to the original samples, the irreversible loss in the first cycle has been greatly reduced, and the discharge capacity has been slightly improved. The shortening of the high-voltage platform proves the suppression of the corresponding H2-H3 phase transition and the enhancement of structural stability, which is expected to bring about an improvement in the retention of cycle capacity.
[0045] Figure 5The following is a comparison chart of the capacity retention rate of 200 cycles of 1C rate of high nickel positive electrode material coated with 3% CoAl lithiated spinel in Example 1. As can be seen from the figure, the 1C discharge capacity of the material (3wt%-NMC92) coated with 3wt% spinel structure is 197mAh / g, and the capacity retention rate after 200 cycles is 81.2%, which is 16.7% higher than that of high nickel positive electrode material (P-NCM92), showing an excellent improvement in capacity retention performance. Moreover, due to the presence of good three-dimensional lithium ion diffusion channels in the spinel structure, the discharge capacity of the modified material at the same rate is greatly improved compared with the original material (183mAh / g→197mAh / g).
[0046] Figure 6 This is a DCR test diagram of high nickel cathode material coated with 3% CoAl lithiated spinel in Example 1. It can be seen from the figure that during 50 cycles, the DCR change rate of the high nickel cathode material (P-NCM92) reached 176.3%, while the DCR change rate of the high nickel cathode material (3wt%-NMC92) after spinel structure coating was reduced to 126.7%. This result shows that the spinel structure coating significantly improves the conductivity and cycle stability of the material.
[0047] Figure 7 This is the EIS test graph after 50 cycles of high-nickel cathode material coated with 3% CoAl lithiated spinel in Example 1. It can be seen from the figure that after the coating treatment, the surface structure of the high-nickel cathode material is significantly optimized, and the electronic and ionic conductivity of the material is improved, thereby reducing the charge transfer impedance inside the battery.
[0048] Example 2
[0049] A method for modifying a CoAl-based lithiated spinel-coated high-nickel positive electrode material comprises the following steps:
[0050] Step 1. Follow the Li2Co 1.6 Al 0.4 The stoichiometric ratio of O4 is 1:1, lithium acetate, cobalt acetate and aluminum nitrate are weighed and dissolved in ethanol, and stirred to dissolve to obtain a modified solution; in the modified solution, the molar concentration of lithium acetate is 11.5 mmol / L;
[0051] Step 2. Disperse the high nickel cathode material in the modified solution prepared in step 1, stir and mix evenly to obtain 50 mL of pink mixed solution; wherein Li2Co 1.6 Al 0.4 O4 accounts for 5wt% of the mass of the high nickel cathode material;
[0052] Step 3. The mixed solution was heated to 80°C, and the mixed solution was evaporated at a stirring speed of 500 r / min and a temperature of 80°C to obtain a powder, and the powder was vacuum dried in a vacuum oven at 80°C for 12 hours to remove the solvent;
[0053] Step 4. Grind the dried powder obtained in step 3, place it in a tube furnace, and sinter it at 450°C for 10 hours in an oxygen atmosphere. The heating rate is set to 5°C / min. After sintering, cool it naturally to room temperature to obtain a CoAl-based lithiated spinel-coated high-nickel positive electrode material (5wt%-NMC92).
[0054] Figure 8 This is the SEM spectrum of the high nickel positive electrode material coated with 5% CoAl lithiated spinel in Example 2. As can be seen from the figure, the spherical particles remain at a size of 10-15μm, but a large number of broken spheres appear in the figure, and a large number of impurity particles appear at the same time. Since the coating method is a sol-gel method, excessive coating material may not be uniformly coated on the spheres and separate impurity particles may appear, thereby affecting the discharge and cycle performance.
[0055] Fig. 9 This is the EDS-Mapping spectrum of the high-nickel positive electrode material coated with 5% CoAl lithiated spinel in Example 2. It can be seen from the figure that the nickel and manganese elements are evenly distributed without segregation, and the cobalt and aluminum elements are partially aggregated due to the appearance of impurity particles.
[0056] Fig.10 This is the XRD spectrum of the high-nickel positive electrode material coated with 5% CoAl lithiated spinel in Example 2. It can be seen from the figure that the sample exhibits a layered structure corresponding to the R3m space group, and no impurity phase appears. The 003 peak and 104 peak ratio of the 5wt% mass ratio coated positive electrode material have significantly decreased, indicating that its lithium-nickel mixed arrangement ratio has increased.
[0057] It should be noted that the above embodiments are only partial embodiments of the preferred embodiments of the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A method for modifying a CoAl-based lithiated spinel-coated high-nickel cathode material, characterized in that: The modification of high nickel cathode material is achieved by forming a CoAl-based lithiated spinel layer on the surface of the high nickel cathode material; the chemical formula of the CoAl-based lithiated spinel is Li2Co 1.6 Al 0.4 O4.
2. A method for modifying a CoAl-based lithiated spinel-coated high-nickel cathode material, characterized in that: The following steps are involved: Step 1. Follow the Li2Co 1.6 Al 0.4 O4 stoichiometric ratio, lithium acetate, cobalt acetate, and aluminum nitrate were weighed and dissolved in ethanol, stirred to obtain a modified solution; In the modified solution, the molar concentration of lithium acetate is 5 mmol / L to 12 mmol / L; Step 2. Disperse the high nickel cathode material in the modified solution prepared in step 1, stir and mix evenly to obtain a mixed solution; wherein Li2Co 1.6 Al 0.4 O4 accounts for 3wt% to 5wt% of the mass of the high nickel positive electrode material; Step 3. Raise the temperature of the mixed solution to 80°C, and evaporate the mixed solution at 80°C under vigorous stirring to obtain a powder, which is then dried; Step 4. Grind the powder dried in step 3, sinter, and naturally cool to room temperature to obtain a CoAl-based lithiated spinel-coated high-nickel positive electrode material.
3. The modification method of the CoAl-based lithiated spinel-coated high-nickel positive electrode material according to claim 2, characterized in that: In step 3, the stirring speed is set to 500-700 r / min.
4. The modification method of the CoAl-based lithiated spinel-coated high-nickel positive electrode material according to claim 2, characterized in that: In step 3, the drying process is carried out in a vacuum environment, the drying temperature is 70 to 90° C., and the time is 10 to 14 hours.
5. The modification method of the CoAl-based lithiated spinel-coated high-nickel positive electrode material according to claim 2, characterized in that: In step 4, the sintering treatment is carried out in an oxygen atmosphere, at a temperature of 400 to 500° C., for a time of 5 to 10 hours.
6. The modification method of the CoAl-based lithiated spinel-coated high-nickel positive electrode material according to claim 2, characterized in that: In step 4, during the sintering process, the heating rate is 3 to 5°C / min.
7. Use of the CoAl-based lithiated spinel-coated high-nickel positive electrode material obtained by the modification method according to any one of claims 1 to 6 in lithium-ion batteries.